2012
DOI: 10.1371/journal.pone.0041104
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Microflora Disruption by Antibiotics Promotes Airway Hyperresponsiveness after Respiratory Syncytial Virus Infection

Abstract: BackgroundRegulatory T cells (Treg cells), which are essential for regulation of immune response to respiratory syncytial virus (RSV) infection, are promoted by pharyngeal commensal pneumococcus. The effects of pharyngeal microflora disruption by antibiotics on airway responsiveness and relative immune responses after RSV infection have not been clarified.MethodsFemale BALB/c mice (aged 3 weeks) were infected with RSV and then treated with either oral antibiotics or oral double distilled water (ddH2O) from 1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Vice versa, respiratory bacteria can also promote viral infection through numerous pathways [112][113][114][115][116] . For example, the upregulation of adhesion receptors, such as intercellular adhesion molecule 1 (ICAM1), was shown to increase the binding of HRV and respiratory syncytial virus (RSV) to epithelial cells and amplify pro-inflammatory responses [114][115][116] .…”
Section: T Helper 17 Cellsmentioning
confidence: 99%
“…Vice versa, respiratory bacteria can also promote viral infection through numerous pathways [112][113][114][115][116] . For example, the upregulation of adhesion receptors, such as intercellular adhesion molecule 1 (ICAM1), was shown to increase the binding of HRV and respiratory syncytial virus (RSV) to epithelial cells and amplify pro-inflammatory responses [114][115][116] .…”
Section: T Helper 17 Cellsmentioning
confidence: 99%
“…The presence of a nasopharyngeal commensal protected mice against RSV-induced airway hyperresponsiveness. RSV-infected mice who underwent antibiotic-mediated depletion of Streptococcus viridans in the nasopharynx exhibited increases in number of inflammatory lymphocytes and airway hyperresponsiveness, and decreases in regulatory T cell number and transforming growth factor-β production ( 103 ). Others have shown that colonization of the URT with S. aureus drastically reduced influenza-induced acute lung injury and mortality in mice by recruiting a C-C chemokine receptor type 2 + cluster of differentiation (CD)11b + monocyte subset to the lungs and inducing an M2 macrophage phenotype ( 104 ).…”
Section: The Respiratory Tract Microbiomementioning
confidence: 99%
“…The relation of respiratory viruses and airway microbiota has been shown to be reciprocal, and ample scientific evidence has demonstrated that airway microbiota can also alter the course of viral infections through the influence that it exerts on the host immune responses. In that respect, data from animal models have shown that commensal microbiome in the URT has a protective function against the airway hyperresponsiveness induced by RSV, and the use of antibiotics that decreases specific populations in the URT microbiome reverts this effect 74 . The same effect has also been found for other respiratory viruses 75 …”
Section: Respiratory Viral Infections As a Risk Factor For Asthma Devmentioning
confidence: 85%